MANAJEMEN KEPEMIMPINAN PADA STARTUP DAN RELEVANSINYA TERHADAP PENGEMBANGAN TENAGA KERJA TVET - Nurtjahyadi Nurtjahyadi; Deviana Ridhani; M. Giatman; Sukardi Sukardi (Jurnal Manajemen Pendidikan, 2026)
The rapid growth of technology-based startups demands adaptive and innovative leadership patterns that significantly influence human resource development. This study aims to examine the effect of leadership management in startups on workforce development within Technical and Vocational Education and Training (TVET). A quantitative approach with an explanatory research design was employed, involving startup managers and TVET stakeholders as respondents. Data were collected through a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that startup leadership management has a positive and significant effect on TVET workforce development, with a path coefficient of 0.79, a t-statistic of 11.42, and a p-value of < 0.001. The coefficient of determination (R² = 0.63) shows that 63% of the variance in TVET workforce development is explained by startup leadership constructs. Specifically, agile leadership (β = 0.31) and digital leadership (β = 0.28) provide the most dominant contributions, compared to transformational leadership (β = 0.21) and entrepreneurial leadership (β = 0.19).These findings confirm that startup leadership practices are highly relevant for integration into TVET systems to enhance technical and non-technical competencies, employability skills, and graduates’ readiness to face the dynamic demands of startup-driven and digital industries. This study contributes theoretically to the integration of leadership and vocational education literature and offers practical implications for TVET managers and policymakers in designing adaptive and sustainable workforce development strategies.